2006
DOI: 10.1029/2005je002613
|View full text |Cite
|
Sign up to set email alerts
|

Bistatic observations of Titan's surface with the Huygens probe radio signal

Abstract: Huygens provided an unanticipated bistatic radio scattering experiment from Titan's surface. After a successful entry and descent on Titan, on 14 January 2005, the probe remarkably survived the landing and continued radioing from the surface to the overflying Cassini, until the orbiter set below Titan's local horizon. Here we report high‐quality measurements of the 2098 MHz (14.3 cm) postlanding radio signal, focusing on the striking variations observed in signal strength. The mechanism that creates this fadin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 14 publications
1
5
0
Order By: Relevance
“…Additional geometric information on the resting position of Huygens Probe from parallax in the camera system, and the sharpness of focus of features on the ground indicates (Karkoschka et al, 2007) that the camera window was 48±2cm above the groundessentially equivalent to the base of the probe being 1±2cm above ground level. This is also consistent with a weaker but entirely independent constraint derived from the multipath interference pattern seen in the probe radio signal, which indicates the phase center of the antenna to be 75±5cm above the ground, or that the base of the probe was 1±5cm above ground level (Pérez-Ayúcar et al, 2006).…”
Section: Huygens Probe Dynamics and Resting Positionsupporting
confidence: 76%
See 1 more Smart Citation
“…Additional geometric information on the resting position of Huygens Probe from parallax in the camera system, and the sharpness of focus of features on the ground indicates (Karkoschka et al, 2007) that the camera window was 48±2cm above the groundessentially equivalent to the base of the probe being 1±2cm above ground level. This is also consistent with a weaker but entirely independent constraint derived from the multipath interference pattern seen in the probe radio signal, which indicates the phase center of the antenna to be 75±5cm above the ground, or that the base of the probe was 1±5cm above ground level (Pérez-Ayúcar et al, 2006).…”
Section: Huygens Probe Dynamics and Resting Positionsupporting
confidence: 76%
“…(Fulchignoni et al, 2005;Grard et al, 2006;Simões, 2007, Hamelin et al, 2007López-Moreno et al, 2008), and revealed the existence of an atypical Schumann resonance that implies the presence of a subsurface water ocean (Béghin, Hamelin and Sotin, 2010). Following the successful landing of Huygens, the operation of PWA was extended for approximately 32 min measuring the electrical properties of the ground until the end of the HASI measurement cycle, and also recording the weak 36 Hz signal of the Schumann resonance (Béghin et al, 2013), while the data link to the orbiter lasted for 40 min more (Pérez-Ayúcar et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Over the past decades, orbital BSR experiments have been used to assess the textural (and in some cases, dielectric) properties of the surfaces of terrestrial bodies such as Mercury 2 , Venus 3 , the Moon 4 6 , Mars 7 , 8 , Saturn’s moon Titan 9 , and now comet 67P/CG 10 . In contrast to most orbital BSR experiments, Dawn’s HGA beam intersected Vesta’s surface at grazing angles of incidence near 89° and in a microgravity environment with substantial variability in its gravity field 11 , leading to a low and variable orbital velocity and hence a more challenging detection of the Doppler-shifted surface echo (hereafter simply referred to as the “surface echo”).…”
Section: Introductionmentioning
confidence: 99%
“…6, with a conservative elevation threshold of 10 o . Depending on the sea state and the antenna beam pattern, such an elevation should be relatively free of multipath effects (which were observed in the Huygens telemetry link to Cassini, Pérez-Ayú car et al, 2006) or atmospheric attenuation. Furthermore, only pathological shoreline topography (i.e.…”
Section: Communications and Science Returnmentioning
confidence: 99%